A Review of the Evolution of the NCS-NCVS Police Reporting and Response Questions and Their Application to Older Women Experiencing Violent Victimization - Addington, Lynn A. (Journal of contemporary criminal justice, 2025)
Little attention is given to the history of the data that underlie research on crime trends and patterns. This article considers the evolution of the National Crime Victimization Survey’s (NCVS) police reporting and response questions. These questions are particularly important as the NCVS is the only nationally representative source of information on whether crime is reported to the police and citizen views of police actions. In addition, the current NCVS redesign is set to substantially add to these items. To provide a context for this discussion, this article applies the police reporting and response questions to an understudied victim group, specifically older women who experience violent victimization. This application illustrates the research opportunities and challenges for working with these data.